Józef Hen, reżyser – światy niedokończone - Gwóźdź, Andrzej (Załącznik Kulturoznawczy, 2022)
The article presents peripeteia connected with Józef Hen’s activity as a film director. And while the writer’s relations with cinema are permanent and diverse (ranging from the role of screenwriter, to being an assistant director, to literary leadership of a film group), Hen was a director only twice: once in a film short story Autobusy jak żółwie (Buses like turtles) in an anthology film Weekendy (Weekends, 1963), and for the second time – as an author of a three-episode TV series Perły i dukaty (Pearls and Ducats, 1965, premiere in 1966). The author of the text traces Hen’s artistic output in the context of film activity of writers-film makers (the so-called scriptwriters’ revolt) in the early 1960s, but also relates it to the writer’s cinephile passion. This particularly refers to the film short story, which is here located in a wide socio-cultural environment associated with the formation of youth culture of the Polish Poeple’s Republic in the period of the “minor stabilization”. Regarding the series of Pearls and Ducats, the author examines the role of television as a medium shaping the poetics and styles of reception of these films. Hen’s work as a film director remains an interesting testimony to the 1960s director’s film worlds, which – although closed – seem to be unfinished.